An international survey of bacterial contamination and householders' knowledge, attitudes and perceptions of hygiene. Issue 4 (July 2013) - Oxford, John; Berezin, Eitan N; Courvalin, Patrice; Dwyer, Dominic; Exner, Martin; Jana, Laura A.; Kaku, Mitsuo; Lee, Christopher; Letlape, Kgosi; Low, Donald E.; Madani, Tariq Ahmed; Rubino, Joseph R.; et al.
This prospective, multinational study was conducted in 20 homes in eight cities or regions in different countries to determine the level of microbiological contamination of common surfaces and items, and investigate the attitudes and perceptions of householders towards cleaning and hygiene. Environmental Health Practitioners took eight standardised swabs in each home. The swabs were cultured for a range of micro-organisms. Householders ( n =160) were also interviewed regarding their cleaning habits and perceptions of hygiene. Overall, 28% of surfaces or items tested in the study had 'moderate bacterial growth' or 'heavy bacterial growth'. Kitchen cloths were the most contaminated items, with 86% having moderate bacterial growth or heavy bacterial growth; kitchen taps were the second most contaminated items, with 52% having moderate bacterial growth or heavy bacterial growth. High proportions (>50%) of kitchen cloths contained coliforms, Enterobacteriaceae and Pseudomonas spp. The visual appearance of surfaces and items frequently (30%) did not correspond to their level of contamination with micro-organisms. The majority of householders (65%) cleaned to make the house 'look clean, smell nice and remove germs'; however, householders' perceptions of the cleanliness of their homes frequently did not correspond to microbiological reality. In conclusion, further research and education are needed regarding hygiene in the home.